DISPERSAL PROPENSITY IN TETRAHYMENA THERMOPHILA CILIATES—A REACTION NORM PERSPECTIVE. (1st August 2014) - Pennekamp, Frank; Mitchell, Katherine A.; Chaine, Alexis; Schtickzelle, Nicolas
Abstract: Dispersal and phenotypic plasticity are two main ways for species to deal with rapid changes of their environments. Understanding how genotypes (G), environments (E), and their interaction (genotype and environment; G × E) each affects dispersal propensity is therefore instrumental for predicting the ecological and evolutionary responses of species under global change. Here we used an actively dispersing ciliate to quantify the contributions of G, E, and G × E on dispersal propensity, exposing 44 different genotypes to three different environmental contexts (densities in isogenotype populations). Moreover, we assessed the condition dependence of dispersal, that is, whether dispersal is related to morphological, physiological, or behavioral traits. We found that genotypes showed marked differences in dispersal propensity and that dispersal is plastically adjusted to density, with the overall trend for genotypes to exhibit negative density‐dependent dispersal. A small, but significant G × E interaction indicates genetic variability in plasticity and therefore some potential for dispersal plasticity to evolve. We also show evidence consistent with condition‐dependent dispersal suggesting that genotypes also vary in how individual condition is linked to dispersal under different environmental contexts thereby generating complex dispersal behavior due to only three variables (genes, environment, and individual condition).